The effect of gelatinase production of Enterococcus faecalis on adhesion to dentin after irrigation with various endodontic irrigants - Mehmet Burak Guneser; Ayce Unverdi Eldeniz (Taylor & Francis Group, 2016)
Objectives: The aim of this study was to evaluate whether the gelatinase production ability of Enterococcus faecalis provides any advantage on adhesion of this bacterium to dentin treated with various irrigants and their combinations. Materials and methods: Standardized dentin discs were randomly divided into five groups (n = 20): group 1: 2.5% sodium hypochlorite (NaOCl), group 2: 2% chlorhexidine (CHX), group 3: NaOCl + Saline + CHX, group 4: NaOCl + EDTA + NaOCl, group 5: QMix. After incubation of dentin discs with irrigants, each group was divided into two subgroups (n = 10) according to the bacterial strains used; a gelatinase-producing and a gelatinase-deficient strain of E. faecalis. After incubation of the discs with the bacterial suspensions aerobically for 48 h, XTT assay was conducted for bacterial adherence evaluation. Data were statistically analyzed by ANOVA and Tukey's HSD tests (p = .05). Results: Gelatinase-producing E. faecalis adhered to dentin was significantly more than gelatinase-deficient E. faecalis in all test groups (p < .05). Adherence to CHX-treated dentin was lower than to the surfaces treated with other irrigants, alone or in combination (p < .05). These differences were significant except for comparisons with QMix for gelatinase-producing bacteria (p < .05). Conclusions: Gelatinase production of E. faecalis may be an important factor for bacterial adhesion. The addition of CHX to the irrigation regimen resulted in fewer adhered bacteria to dentin. QMix was not as effective as CHX in terms of bacterial adhesion prevention.